2021
DOI: 10.1097/txd.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Between SARS-CoV-2–specific Cell-mediated and Antibody Responses Elicited by mRNA-1273 Vaccine in Kidney and Liver Transplant Recipients

Abstract: Infectious DiseaseBackground. Severe acute respiratory syndrome coronavirus 2-specific cell-mediated immunity (SARS-CoV-2-CMI) elicited by mRNA-based vaccines in solid organ transplant (SOT) recipients and its correlation with antibody responses remain poorly characterized. Methods. We included 44 (28 kidney, 14 liver, and 2 double organ) recipients who received the full series of the mRNA-1273 vaccine. SARS-CoV-2-CMI was evaluated at baseline, before the second dose, and at 2 wk after completion of vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 40 publications
(99 reference statements)
1
54
0
1
Order By: Relevance
“…We did not study cellular responses to vaccination, and these may be discordant with humoral responses. 10,27 We also studied responses at an early time point only; a high early peak in antibody titres following vaccination is not necessarily an indicator of durable response. 36 As with any observational study, we cannot exclude the possibility that some of the associations we report might be explained by residual or unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We did not study cellular responses to vaccination, and these may be discordant with humoral responses. 10,27 We also studied responses at an early time point only; a high early peak in antibody titres following vaccination is not necessarily an indicator of durable response. 36 As with any observational study, we cannot exclude the possibility that some of the associations we report might be explained by residual or unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
“…3 Existing studies investigating determinants of vaccine immunogenicity have reported that lower antibody responses following SARS-CoV-2 vaccination associate with administration of viral vector vs messenger RNA (mRNA) vaccines, older age, poorer general health, immunosuppression and shorter inter-dose intervals. [4][5][6][7][8][9][10][11] Higher postvaccination antibody titres are seen in those with evidence of SARS-CoV-2 infection before vaccination. 9,12,13 However, these studies are limited in several respects: many are conducted in specific populations such as health care workers 5,9,12,13 or in individuals with a particular demographic or clinical characteristic that may influence vaccine immunogenicity, 6,10,11 which may constrain generalisability of their results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the administration of mRNA vaccines has effectively reduced COVID-19-related severe disease, hospital admissions, and mortality in healthy adults [44][45][46], vaccine efficacy has not been as high in other target populations. In fact, different studies have reported lower rates of immune responses after vaccination in patients with hematologic pathologies (chronic lymphatic leukemia, multiple myeloma, lymphoma, and myeloproliferative malignancies) [47][48][49][50], as well as in solid organ transplant recipients [51][52][53][54]. In this scenario, it may be interesting to have new alternative therapies available that focus on increasing the individual immune response against the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%